Haemophilus Aphrophilus Associated Spleen Abscess: An Unusual Presentation of Subacute Endocarditis - Tien, Ya-Chih (Elmer Press, 2012)
The HACEK group of bacteria (Haemophilus spp., Actinobacillus actinomycetemcomitans, Cardiobacterium hominis, Eikenella corrodens, Kingella spp.), is uncommon pathogens of infective endocarditis, but can cause life-threatening events such as heart failure or formation of lethal emboli. Here we report a 58-year-old Asian man with a past history of congenital valvular heart disease who presented with sudden onset of left flank pain followed by fever with chills for 2 weeks. Abdominal computed tomography (CT) indicated a 1.6 cm abscess in the spleen. Culturing indicated the presence of Haemophilus aphrophilus. We diagnosed the patient with subacute endocarditis complicated with spleen abscess. The patient recovered fully after two weeks antibiotic (Ceftriaxone) treatment. Clinicians should give further attention to infective endocarditis caused by bacteria in the HACEK group in patients with metastatic infection such as spleen abscess with suspected valvular heart disease.